To proove the following

Asked by  | 3rd Mar, 2008, 09:59: PM

Expert Answer:

Join OA, OB and OC

Area of triangle AOB = 1/2 x AB x OR

Area of triangle AOC = 1/2 x AC x OQ

thus, ABx OR + AC x OQ = 2(Area of triangle AOB + Area of triangle AOC)

                                            = 2(Area of triangle ABC - Area of trinagle BOC)

                                            = 2(1/2 x BC x AS - 1/2 x BC x OP)

                                            = BC (AS-OP)

                                            = BC (AS-TS)   [because TS = OP)

                                            = BC x AT  hence, proved

Answered by  | 25th Jun, 2008, 04:38: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.